Students' Perception on Jigsaw Cooperative Learning Strategy in Teaching and Learning Activities at the Eleventh Grade - Rahmi; Muhammad Tahir; Andi Anto Patak (International Journal of Language, Education, and Literature, 2025)
This study aims to investigate and evaluate how students at SMAN 4 Takalar perceive the challenges they face and how they are resolved when teaching descriptive text writing, especially in the wake of the covid-19 pandemic, using the Jigsaw model cooperative learning strategy. Traditional teaching and learning environments were drastically changed by the global pandemic, which created new challenges for both teachers and students, particularly in skill-based areas like writing. Students frequently struggle with descriptive text writing because it requires careful attention to detail, a comprehensive vocabulary, and logical arrangement. By encouraging active participation, peer-to-peer instruction, and cooperative problem-solving, the Jigsaw model, a cooperative learning approach in which students become “experts” on a portion of the material before teaching it to their peers is proposed as a potentially successful tactic for minimizing these learning difficulties. Particularly, this study looks into how students perceive the challenges that come with writing descriptive texts and how the Jigsaw method either helps them get outside existing challenges or creates new ones. Data will be collected through in-depth interviews, and documentations with eleventh-grade students at SMAN 4 Takalar using a qualitative research methodology. The anticipated findings will provide insight on how students explicitly perceive challenges in producing descriptive texts (such as vocabulary acquisition, idea development, organization, and grammar) and offer insights into how the Jigsaw technique affects these perceived issues. Students are expected to report advantages like higher confidence, better structural comprehension through collaborative text construction, and expanded vocabulary through peer interaction. On the other hand, the study will also find out what new challenges students have when using the Jigsaw strategy in a post-pandemic context, like adapting to group projects following extended periods of distance learning, controlling group dynamics, or ensuring personal responsibility. This study has significant implications for creating better and successful writing instruction strategies in the changing educational environment, providing useful advice for English teachers in Indonesia.